MALAYSIA-SINGAPORE MARITIME DELIMITATION: A COMPLEX PATH OF RESOLUTION? - Salma Yusof; Mazura Md Saman; Khairul Nizam Taib (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The Malaysia-Singapore delimitation issue has continued to be an intricate and significant bilateral concern since the 2008 decision by the International Court of Justice (ICJ) on Batu Puteh. The 2008 judgment was perceived as removing at least one of the obstacles for Malaysia, Singapore and Indonesia to establish clear boundaries for their maritime territories in the Singapore Strait. Yet, the ruling also creates “grey area” in which maritime delimitation on overlapping territorial waters between Malaysia and Singapore need to be resolved. The delimitation becomes more complex with the awarding of Middle Rocks to Malaysia. Indonesia’s potential involvement in future negotiation adds an additional level of complexity. This is a qualitative study, employing content analysis and literature study methodology. The study aims to analyse and examine Malaysia’s outstanding maritime delimitation issue with Singapore. It is submitted that the Malaysia-Singapore maritime delimitation is a complex issue with historical, legal and geographical dimensions. While efforts have been made to address and manage the issue, achieving a comprehensive resolution remains a challenging task. Both parties seem to continue navigating the complexities of their maritime delimitation issue with a blend of legal frameworks, diplomatic negotiations and mutual cooperation. It is imperative for both parties to expedite the negotiating process and achieve a definitive agreement on the delimitation boundary in the vicinity of Batu Puteh.